A influência dos aspectos visuais da embalagem na formação das atitudes do consumidor: Um estudo no setor de alimentos - Garrán, Vanessa Gabas (2006)
Packages have drawn attention as an important tool in the marketing mix. It has been a long time since they are not considered just for their basic functions, such as keeping, protecting and transporting the product. Nowadays, their promotional role has gained importance and, in many cases, the package represents the only communication tool to the consumer market. This work aims to understand the visual characteristics of food packages (cookies) and their possible influence on the formation of consumer attitudes, represented by cognitive, affective and behavior components. The literature survey allowed concluding that a broad and generally accepted conception of the term attitude is the one which considers it as a general favorable or unfavorable evaluation of an object, formed by beliefs and emotions evoked by it. This evaluation becomes evident through the individual s behavior (behavior component). In order to reach the proposed objective an exploratory and qualitative research has been chosen. In-depth interviews were made using a non-probabilistic sample, selected by convenience. The interviewees could talk about which package attributes they considered more important and, out of such results, it was possible to interpret the exposed opinions utilizing the content analysis technique. Through the categorization of registering units (sentences) obtained in the course of the interviews it was possible to make a comparison between these units and the consumer attitude theory. The results of the research suggest that the visual characteristics of the packages used in the interviews provoke opinions, sensations and inferences regarding product attributes (cookies), what demonstrates the existent relation between colors, illustrations, shapes, texts, drawings and some other visual aspects of the packages and the development of beliefs, emotions and behavior intentions of the consumer